Structural Models of the Dollar - Adams, Charles (IMF Working Papers; Working Paper, 1990)
This paper addresses several questions about the time series processes followed by dollar exchange rates. The stochastic process for exchange rates implied by structural models and the conditions under which they would be described by random walks are examined. Tests on the univariate time series for dollar exchange rates are undertaken to determine if there is evidence for departures from a random walk. Multivariate tests examine whether longer-run movements in the dollar are linked to those in other economic variables, and whether deviations from these long-run relationships contain information for predicting exchange rate movements.